Step-by-step explanation:
well,
(y - 7)² = (y - 7)(y - 7)
remember how to multiply 2 expressions ?
you have to multiply every term of one expression with every term of the other expression and sum the results all up (incl. considering their individual signs, of course).
so, when we do the multiplication, we get
(y - 7)(y - 7) = y×y - 7×y - 7×y + (-7)×(-7) =
= y² - 14y + 49
and that is clearly different to y² - 49
FYI
y² - 49 is the result of
(y - 7)(y + 7)
because
y×y + 7×y - 7×y + (-7)(7) = y² - 49
Hey there!
Let's solve the equation.
20=6x+14
Subtract 14 from both sides.
6=6x
Divide 6 on both sides.
x=1
This is false.
I hope this helps!
~kaikers
Factors of 56 are: 1, 2, 4, 7, 8, 14, 28, 56
<span>Factors of 84 are: 1, 2, 3, 4, 6, 7, 12, 14, 21, </span>28, 42, 84
The outside term multiplies by the outside term on the oposite side to equal the answer.
Example:
Look at the factors of 84
84X1=84
2X42=84
3X28=84
and so on!
A bisector splits an angle into two equal angles.
The answer is the last one: it splits the angle into two congruent angles.